Power frequency electromagnetic fields management technologies - Farag A.; Said I.; Hussain H.; Ahmad A.S. (2023)
Electrical and magnetic fields are complex entities, much more than chemical agents. While exposure to chemicals can often be adequately described by the total amount ingested over some period of time, many more parameters must be considered for fields. Exposures are complicated by movement through fields, spatial variations, and other possible exposure parameters. Field management minimizes the impact that magnetic or electric fields have on their surroundings, may involve (i) measurement programs, (ii) prudent avoidance, (iii) site arrangement, (iv) design change, (v) cancellation, and (vi) shielding or a combination of these methods. This paper provides insight to several field-management strategies developed for if needed. The paper considered six distinct sources, which are transmission lines, distribution lines, substations, building wiring, appliances and transportation systems. Each source presented a unique set of limitations and possibilities for field management options. The effectiveness, cost, environmental impact, safety concerns of field management options were considered for each source.